2014
DOI: 10.1039/c4nr00868e
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of the application of chalcogenide nanoparticles in polymer solar cells

Abstract: In this review the use of solution-processed chalcogenide quantum dots (CdS, CdSe, PbS, etc.) in hybrid organic-inorganic solar cells is explored. Such devices are known as potential candidates for low-cost and efficient solar energy conversion, and compose the so-called third generation solar cells. The incorporation of oxides and metal nanoparticles has also been successfully achieved in this new class of photovoltaic devices; however, we choose to explore here chalcogenide quantum dots in light of their par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 181 publications
(205 reference statements)
0
49
0
2
Order By: Relevance
“…128 Nesta configuração de célula, uma única camada fotoativa é preparada através da mistura de PQs com polímeros conjugados, ou PQs e polímeros são alternadamente dispostos em camadas separadas para construir uma célula de configuração plana ou de bicamadas. 129,130 Na interface PQ/polímero fica a separação de cargas e ela é ditada pelos seus níveis de energia. Devido à baixa mobilidade do portador de carga dos polímeros orgânicos semicondutores, a espessura da camada fotoativa fica restrita, limitando a eficiência das células.…”
Section: Células Solares Híbridas -Ponto Quântico/polímerounclassified
See 1 more Smart Citation
“…128 Nesta configuração de célula, uma única camada fotoativa é preparada através da mistura de PQs com polímeros conjugados, ou PQs e polímeros são alternadamente dispostos em camadas separadas para construir uma célula de configuração plana ou de bicamadas. 129,130 Na interface PQ/polímero fica a separação de cargas e ela é ditada pelos seus níveis de energia. Devido à baixa mobilidade do portador de carga dos polímeros orgânicos semicondutores, a espessura da camada fotoativa fica restrita, limitando a eficiência das células.…”
Section: Células Solares Híbridas -Ponto Quântico/polímerounclassified
“…A mais alta eficiência foi conseguida por Ren e colaboradores e atingiu a marca de 4,1% com a utilização de pontos quânticos de CdS. 130 Apesar dessas células híbridas não terem se desenvolvido tão bem quanto outras células de baixo custo, elas possuem grandes possibilidades de atingir um melhor desempenho em sistemas ternários, uso de nanopartículas em redes de aerogéis e manipulação química da superfície da célula.…”
Section: Células Solares Híbridas -Ponto Quântico/polímerounclassified
“…It was also shown that charge separation occurs quickly if the exciton is generated in a CdSe branch, which is in direct contact with the P3HT phase. 166, 167 Interesting results were also achieved for various heterostructured hyperbranched nanostructures. For example, OA-capped CdSe, CdTe, and type-II heterostructured CdTe/CdSe nanotetrapods have been used to fabricate polymer-inorganic hybrid solar cells with the blend of tetrapod NCs and P3HT.…”
Section: Solar Cellsmentioning
confidence: 93%
“…Some of the expected advantages are (1) a contribution to light absorption by an inorganic acceptor can lead to the generation of more photocarriers, due to their larger linear absorption coefficients compared to those of fullerene derivatives; (2) the absorption of nanoparticles can be tuned to cover a broad solar spectral range, as a result of modification of their size and shape, complementary to that of the organic electron donor/hole transporter; (3) the physical dimensions of some inorganic semiconductors can be tailored to produce 1-D nanostructures, to allow efficient exciton dissociation, i.e., charge separation and electron transporting pathways simultaneously; (4) ultrafast and efficient photoinduced charge carrier transfer between the electron acceptor (inorganic nanoparticles) and the electron donor (the organic semiconductor); (5) the acceptors have relatively high electron mobility; and (6) good photo-and chemical stability. 91 However, to date, PCEs achieved for hybrid organic-inorganic solar cells are significantly lower than those of OPV devices, which is primarily due to the challenges in controlling the interface between the nanoparticles and the polymer, and achieving a well-defined matrix with a continuous percolation network. Furthermore, the presence of surface traps on the nanoparticles can be problematic for achieving good charge generation and carrier transport.…”
Section: Organic and Hybrid Solar Cellsmentioning
confidence: 99%
“…These devices have the potential to reduce manufacturing costs due to their solution processability, light weight, and being amenable to large area deposition. CQDs can be utilized in Schottky, 118,119 p-n heterojunction, 120,121 hybrid BHJ, 91 and as the sensitizers in PEC solar cells. 122 CQDs are nanometer-sized particles that are below the Bohr exciton radius of the specified material.…”
Section: -114mentioning
confidence: 99%